2013
DOI: 10.1103/physreva.88.053619
|View full text |Cite
|
Sign up to set email alerts
|

Topological phase transitions driven by non-Abelian gauge potentials in optical square lattices

Abstract: We analyze a tight-binding model of ultracold fermions loaded in an optical square lattice and subjected to a synthetic non-Abelian gauge potential featuring both a magnetic field and a translationally invariant SU(2) term. We consider in particular the effect of broken time-reversal symmetry and its role in driving non-trivial topological phase transitions. By varying the spin-orbit coupling parameters, we find both a semimetal/insulator phase transition and a topological phase transition between insulating p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 67 publications
1
30
0
Order By: Relevance
“…(16) is expressed in the basis of the two intermediate bands, but it is also related to the spin degrees of freedom σ and it links the expectation value of the spin to the momentumk around the double-Weyl points. Similarly to what happens in 1D [74] and 2D [55] setups with the simultaneous presence of magnetic fluxes and non-Abelian…”
Section: A Double-weyl Pointsmentioning
confidence: 73%
See 1 more Smart Citation
“…(16) is expressed in the basis of the two intermediate bands, but it is also related to the spin degrees of freedom σ and it links the expectation value of the spin to the momentumk around the double-Weyl points. Similarly to what happens in 1D [74] and 2D [55] setups with the simultaneous presence of magnetic fluxes and non-Abelian…”
Section: A Double-weyl Pointsmentioning
confidence: 73%
“…In previous works, theoretical investigations have shown that synthetic non-Abelian gauge potentials are an efficient way of implementing exotic quantum Hall systems [44][45][46][47][48][49][50] or topological phases [51][52][53][54][55] in two-dimensional lattices, and that laser assisted tunneling may provide useful tools for the simulation of particles like massless Dirac fermions [45], Wilson fermions [56] or Weyl fermions [57].…”
Section: Introductionmentioning
confidence: 99%
“…In the Letter we focus on the effects induced by the non-zero masses of the components, whereas the detailed analysis of massless non-Abelian model can be found in Ref. [31]. In the following we assume t x = t y = 1.…”
Section: Transverse Hall Conductivitymentioning
confidence: 99%
“…] is a periodic function of m [31]. After the substitution the Schroödinger equation reduces to a generalized Harper equation and therefore we should expect a spectrum of the Hofstadter butterfly type [3,4,15].…”
Section: Transverse Hall Conductivitymentioning
confidence: 99%
“…It is widely accepted among the cold-atom community that the system of a two-component Fermi gas with swave attraction in square optical lattice with an external non-Abelian gauge field (or a synthetic Rashba SOC) and out-of-plane Zeeman field can be described by a negative-U Hubbard model [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. We restrict the discussion to the case of atoms confined to the lowest-energy band † 푖,휎 = (1/ ) ∑ k exp(− k.r 푖 ) † k,휎 ( 푖,휎 = (1/ )∑ k exp( k.r 푖 ) k,휎 ) creates (destroys) a fermion on the lattice site r 푖 with pseudospin projection .…”
Section: Introductionmentioning
confidence: 99%